The Impact of Media in Cancel Culture Phenomenon - Graciela Bianca Jaafar; Herna Herna (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
The life of our societyÂ  has goneÂ  through enough changes along with the development of technology. One of the changes that can be felt isÂ  the appearance of digital culture such as Cancel Culture, an action where netizensÂ  boycott a celebrity or a certain public figure due to his/herÂ  taboo action. The purpose of this research is to know the role of the media in the cancel culture phenomenon by using Determination Technology theory. ThisÂ  study usesÂ  descriptive qualitative approaches withÂ Â  virtual ethnography . The scope of the research l focusesÂ  on the Cancellation phenomenon of theÂ  Instagram accounts of @arawindak and @kite..entertainment for two reasons. The first reason is the alleged cancellation of "Arawinda" known as the â€œpelakorâ€ (a married woman whoÂ  engages in adultery withÂ Â Â  a man other than her husband )Â  who received the attention of the Indonesian media and society resulting in easy access to related data regarding Cancel Culture. The second reason isÂ  the lack of scientific studies about Cancel Culture especially on Instagram. The large amountÂ  of data and the analysis that would be required to study the Cancel culture as a whole in a qualitatively extensive manner will resultÂ  in a lack of clarity of the end results. Researchers also held interviews with 5 informants (2 informants who did not engage in cancel culture and 3 informants who engaged inÂ  the cancel culture). The results of this study find that the media plays an important role in the cancel culture phenomenon through social media. The media plays a role in accelerating the boycott process in view ofÂ  the characteristics of social media, which are not restricted to time and space. Thus,Â Â  it can reach even more members than boycotts that occur in the real world. The impact felt through the cancel culture phenomenon carried in the media is even bigger and permanent. Therefore, through this research, it is hoped that people will be more careful in their actions and understand the concept of cancel culture.